2007
DOI: 10.1016/j.febslet.2007.11.053
|View full text |Cite
|
Sign up to set email alerts
|

Epac signaling pathway involves STEF, a guanine nucleotide exchange factor for Rac, to regulate APP processing

Abstract: The amyloid precursor protein (APP) is a key protein involved in the development of Alzheimer's disease. We previously identified a signal transduction secretory pathway in which the small G protein Rac sets downstream of the cAMP/Epac/ Rap1 signalling cascade regulating the a cleavage of APP [Maillet, M. et al. (2003) Crosstalk between Rap and Rac regulates secretion of sAPPa. Nat. Cell Biol. 5, 633-639]. We now report that Rap1 can physically and specifically associate with the guanine nucleotide exchange fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Rac1 has also been identified as a downstream effector of Epac/Rap1 in the release of amyloid precursor protein from transfected CHO cells (49). Subsequent studies revealed that Rap1 interacts with the Rac1-specific guanine exchange factor STEF in this system (50). Interestingly, Rac1 has been implicated in release of WPBs (51).…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 has also been identified as a downstream effector of Epac/Rap1 in the release of amyloid precursor protein from transfected CHO cells (49). Subsequent studies revealed that Rap1 interacts with the Rac1-specific guanine exchange factor STEF in this system (50). Interestingly, Rac1 has been implicated in release of WPBs (51).…”
Section: Discussionmentioning
confidence: 99%
“…Although, additional GEFs from the Dbl family of exchange factors such as Tiam-1 and STEF are capable of activating Rac 1 (28,54), these GEFs have not been reported as being activated by tyrosine phosphorylation, but rather Tiam-1 was reported being activated by threonine phosphorylation (30), whereas STEF was reported being activated by serine/threonine phosphorylation (31). Even so, their effects on PYGM activity were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another recent study reported Epac activation in the nucleus accumbens interfered with conditioned place preference learning (Park et al 2014). In broader learning and memory contexts, changes in Epac regulation have been implicated in the underpinnings of Alzheimer's disease (McPhee et al 2005;Zaldua et al 2007;Grandoch et al 2010), schizophrenia (Kelly et al 2009), and autism (Srivastava et al 2012).…”
mentioning
confidence: 94%